KUALITAS PELAYANAN PENCATATAN NIKAH DIKANTOR URUSAN AGAMA KECAMATAN PARINGIN PADA MASA PANDEMI COVID 19 - Paulina, Siti (Al Iidara Balad, 2021)
This study aims to determine the quality of services in the Office of Religious Affairs (KUA) Paringin sub-district. The method used is descriptive with qualitative analysis. Data collection techniques are observation, documents and interviews. The informants in this study were four KUA employees and five catin who carried out the marriage. The results of this study indicated the services that has been provided by the KUA to catin in the process of registering marriages is good. These results are based on an analysis of six service quality indicators according to Zeithmal, et al in Hadriansyah (2011: 47), namely: competence, reliability, credibility, access, tangible, and responsiveness. Based on the competence aspect, the Office of Religious Affairs (KUA) of the Paringin sub-district has good knowledge and skills in providing services. It included in terms of providing information about the marriage registration process, requirements and delivering information about changes to existing regulations related to the covid-19 pandemic. Then, based on the aspect of reliability, the Office of Religious Affairs (KUA) of the Paringin sub-district was able to create the promised services accurately and responsively. According to the time accuracy, the service of the Office of Religious Affairs (KUA) in Paringin sub-district is not good. It is related with employees presence list during working hours. In the aspect of credibility, the Office of Religious Affairs (KUA) Paringin sub-district carries out services correctly and it is accordance with work procedures and specified time standards to attract public trust in providing services, especially services in marriage registration. In the aspect of access, the Office of Religious Affairs (KUA) Paringin sub-district provides good, fast and easy services to help people who need marriage registration services. According to the tangible aspect, the Office of Religious Affairs (KUA) Paringin sub-district provides adequate service facilities however there are some facilities that have minimum criteria, such as the absence of a television, the lack of a fan and the absence of a chair in front of the KUA. In the aspect of responsiveness, the Office of Religious Affairs (KUA) of the Paringin sub-district is spry and responsive in providing services to catin.